105k views
2 votes
Which expressions are equivalent to 6^16? Check all that apply. (6^8)^2 is the last answer.

Which expressions are equivalent to 6^16? Check all that apply. (6^8)^2 is the last-example-1

2 Answers

4 votes

The fourth and last are correct.


One you have and exponent of an exponent, the base stays the same and the exponents get to be multiplyied:



\bf~(y^(x))^(z) = y^(xz)


Both -8 x -2 and 8 x 2 equal 16.


Answer:



\boxed{\bf~The~fourth~and~last~options~are~correct.}



Hope it helped,


Happy homework/ study/ exam!

User Bryan Roth
by
5.0k points
1 vote

Answer:


(6^(-4))^(-4)=(6^(-2))^(-8)=(6^(8))^(2)=6^(16)

Explanation:

Given:
6^(16)

We need to correct option equivalent to
6^(16)

#1
(6^0)^(16)

Using exponent property,
(a^m)^n=a^(mn)


(6^0)^(16)=6^(0* 16)\Rightarrow 6^0\\eq 6^(16)

False

#2
(6^8)^(8)

Using exponent property,
(a^m)^n=a^(mn)


(6^8)^(8)=6^(8* 8)\Rightarrow 6^(64)\\eq 6^(16)

False

#3
(6^(-4))^(-4)

Using exponent property,
(a^m)^n=a^(mn)


(6^(-4))^(-4)=6^(-4* -4)\Rightarrow 6^(16)= 6^(16)

True

#4
(6^(-2))^(-8)

Using exponent property,
(a^m)^n=a^(mn)


(6^(-2))^(-8)=6^(-2* -8)\Rightarrow 6^(16)= 6^(16)

True

$5
(6^(-1))^(16)

Using exponent property,
(a^m)^n=a^(mn)


(6^(-1))^(16)=6^(-1* 16)\Rightarrow 6^(-16)\\eq6^(16)

False

$6
(6^(8))^(2)

Using exponent property,
(a^m)^n=a^(mn)


(6^(8))^(2)=6^(8* 2)\Rightarrow 6^(16)= 6^(16)

True

Hence,
(6^(-4))^(-4)=(6^(-2))^(-8)=(6^(8))^(2)=6^(16)

User Marse
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.